STUDYING THE CHARACTERISTICS OF STRUCTURAL AND GEOMETRIC PARAMETERS OF THE LEFT VENTRICLE IN PATIENTS WITH CHRONIC KIDNEY DISEASE AND ARTERIAL HYPERTENSION IN THE BACKGROUND OF OBESITY (World Bulletin of Public Health, 2024)
The results of a survey of patients with CKD and metabolic syndrome indicate that the identified disorders of diastolic renal function worsened as the functional state of the kidneys worsened and the metabolic syndrome developed. The identified data support the consideration of kidney function parameters as one of the earliest markers of increased risk of cardiovascular complications in metabolic syndrome, as well as in determining treatment tactics for this category of patients.
Keywords: chronic kidney disease; degree of obesity; arterial hypertension